Evolution of Orofacial Symptoms and Disease Progression in Idiopathic Parkinson’s Disease: Longitudinal Data from the Jönköping Parkinson Registry - Seyed-Mohammad Fereshtehnejad; Örjan Skogar; Johan Lökk (Parkinson's Disease)
Background. Orofacial symptoms are common in Parkinson’s disease (PD) both as initial manifestations and late markers of disease complications. We aimed to investigate the evolution of orofacial manifestations and their prognostic value throughout PD progression. Methods. Data was obtained from “Jönköping Parkinson Registry” database on routine care visits of 314 people with idiopathic PD in southern Sweden. Information on baseline symptomatology, orofacial features, UPDRS, and medications was recorded at baseline and during each follow-up visit within an average of 4.2 (range: 1–12) years. Results. Hypomimia, affected speech, drooling, and impaired swallowing were present in 37.3%/91.6%, 14.1%/65.5%, 11.7%/55.3%, and 10.2%/34.5% at baseline/follow-up, respectively. Male sex [OR = 2.4 (95% CI: 1.0–5.9)], UPDRS motor scores [OR = 1.2 (95% CI: 1.1–1.3)], dominant rigidity [OR = 5.2 (95% CI: 1.4–19.1)], and autonomic disturbance [OR = 3.4 (95% CI: 1.1–10.9)] were risk factors for drooling. Individuals with more severe orofacial burden at baseline had shorter median time to develop UPDRS-Part III > 28 [3rd tertile = 4.7 yr, 2nd tertile = 6.2 yr, and 1st tertile = 7.8 yr; p = 0.014]. Conclusions. Majority of people with PD manifest orofacial manifestations at either early or late stages of the disease. PD severity, symmetry of motor disturbances, and autonomic disorders correlate with orofacial symptoms. Individuals with more severe orofacial burden at baseline progressed faster to more advanced stages.